Study Of Primary Metabolites And Antimicrobial Activity Of Gomphrena Celosioides Mart - NEHA SHARMA,; REKHA VIJAYVERGIA, (International Journal of Pharma and Bio Sciences, 2011)
The quantification of primary metabolites and antimicrobial activities of medicinal plant Gomphrena celosioides Mart. against clinical isolates, Escherichia coli, Pseudomonas aeroginosa and Staphylococcus aureus were investigated. The maximum levels of soluble sugars, lipids and phenols were found to be higher in stem, starch and proteins in roots, as compared to other parts of the plant. The methanolic extract of leaf, stem and root were found to be most effective against the three tested bacteria. The stem and leaf extract were found to have maximum zone of inhibition against E. coli. Root extract showed significant activity against P. aeroginosa. The activity index of the stem and leaf extracts were recorded maximum for E. coli and the root and leaf extracts showed minimum activity index against P. aeruginosa. This research supports the local use of this plant for therapeutic purposes against bacterial infection.